Is body weight-support treadmill training effective in increasing muscle trophism after traumatic spinal cord injury? A systematic review - Do Espirito Santo C.C.* (2015)
© 2015 International Spinal Cord Society.Study design: Systematic review. Objective: To determine the effectiveness of body weight-support treadmill training (BWSTT) for muscle atrophy management in people with spinal cord injury (SCI). Setting: Studies from multiple countries were included. Methods: The following databases were consulted from January to October 2013: PubMed, Institute for Scientific Information (ISI), Science Direct and Lilacs. The methodological quality of the articles included was classified according to Jovell and Navarro-Rubio. Results: A total of five studies were included. These studies reported a significant association between BWSTT and increased trophism of the lower limb muscles of humans with SCI, which was observed as an increase in the cross-sectional area. Moreover, improvements in the ability to generate peak torque, contract the knee extensors and ankle plantarflexors with reduction of body weight support were observed after BWSTT. Conclusion: The results were considered inconclusive because of the low methodological quality of the articles, which was because of the absence of sample homogeneity, thereby providing a low level of evidence for clinical practice.